Yield Improvement of Upland Rice Planted between Oil Palm Using Organic Matter - Eliartati Eliartati; R S Anggraini; A Sofia (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
The application of organic matter is a way to improve upland rice productivity that grows among immature oil palm plants. To improve the yield of upland rice among immature oil palm plants, this study has been carried out by providing organic matter. The research aimed to determine the effect of organic matter application for upland rice production that plant among immature oil palm. The experimental design used in this study was Randomized Block Design with 5 treatments and 4 replications. The treatment includes: control, rice straw compost, weed biomass compost, palm oil empty bunch compost, and cow manure. The dose of organic matter given was 3 tons/ha. The results showed that the application of organic materials have significant effects on yield component and the production of upland rice. In general, the best yield and yield components were obtained in the manure treatment, namely plant height 104.7 cm; the number of productive tillers 158 grains; the percentage of filled grain per panicle was 85.8% and grain yield was 5.6 tons/ha or increase by 21.74% compared to the control treatment (4.6 tons/ha). The highest number of productive tillers and weight of 1000 grains were obtained in the palm oil empty bunch compost treatment (14.5 and 28.2 g).